The Latent Perception of Pregnancy - Borovoi, Leah; Shiloh, Shoshana; Alidu, Lailah; Vlaev, Ivo (Frontiers in Psychology, 2022)
Background: The main purpose of this study was to describe the latent structure of pregnancy perception. Other aims were to discover the roles of risks and medical examinations in pregnancy perception and to compare between men and women, participants who are pregnant and those who are not in their perception of pregnancy. Methods: Study 1 developed the questionnaire by asking 29 young adults an open question about their perception of pregnancy and, based on their responses, generated questions. In Study 2 this questionnaire was distributed among 290 participants (mean age 29.3; standard deviation = 7.5). Results: The statistical clustering analysis revealed 3 major clusters of pregnancy perceptions: 'evaluative', ‘physio-medical’ and 'future considerations', each of them encompassing several meaningful sub-clusters. This structure of pregnancy perceptions supports Beck and Beck-Gernsheim’s modernization approach. Negative emotions towards pregnancy were related to social cognitions, whereas thoughts about risks were included in the medical sub-cluster. After reliability analyses, comparisons of scale scores revealed that women experienced more positive emotions, thought more about physical symptoms and about future issues compared to men (evolutionary explanation was offered). Conclusions: Pregnant participants felt less ambivalence towards pregnancy, thought more about risks and medical examinations and less about parents’ duties than non-pregnant participants. These findings are discussed in relation to Construal Level Theory (Trope and Liberman).